Characterizations of Joker: A Comparison of Two Batman Films - Ni Made Mira Wardhaningsih (Passage, 2017)
Batman franchise is one of the most watched franchises in the history of cinema (Box Office Mojo, 2016). There are at least nine film adaptations of Batman, not including the direct-to-video films, animated films, and television series. There are more than one version of the characters which are consumed by the audience. This study seeks to investigate the portrayals of the Batman villain character Joker in two Batman films entitled Batman (Burton, 1989) and The Dark Knight (Nolan, 2008). Using a qualitative descriptive method, this study employs Boggs and Petrie’s (2008) framework of characterization in films as its analytical tool. Some of Bordwell and Thompson’s (2010) cinematic techniques (i.e., mise-en-scene, camera shot and angle, and sound) are used to strengthen the analysis. The analyses of the portrayals are used to find the signification. The analyses show that the portrayals of Joker have similar traits. However, the portrayals also possess significant differences. Joker in Batman seems to depict human’s corrupted traits whereas Joker in The Dark Knight implies that he is an embodiment of terror. The character Joker is portrayed differently in two different films in order to signify different fears which are circulated in two different time periods. This study reveals that characters based on the same source can signify different representations of fear within the society due to the different time periods the films were produced.Keywords: Batman, character and characterization, cinematic techniques, Joker